Building new capital cities in Africa: Lessons for new satellite towns in developing countries. Issue 4 (2nd October 2017) - Abubakar, Ismaila Rimi; Doan, Petra Leisenring
ABSTRACT: New town building is currently re-emerging in the Third World to decant major metropolitan areas using modernist design and planning assumptions. Using the experience of Africa's postcolonial new capital cities of Abuja (Nigeria), Dodoma (Tanzania), Gaborone (Botswana) and Lilongwe (Malawi), this article analyses the effectiveness of new town building as an urbanisation strategy in Africa and highlights some lessons for new satellite towns in developing countries. Based on extensive analysis of secondary data, plans and empirical studies, the article finds that in addition to their inability to provide adequate housing and infrastructure, these new capital city projects are very expensive and overwhelmed by rapid urbanisation, emphasise physical development, exacerbate social exclusion, disrupt informal settlements and businesses, and lack public involvement. The article concludes by suggesting that new town building in the Global South should learn from the experience of the reviewed cases and focus more on meeting contemporary urban challenges such as rapid urbanisation, informality, social exclusion, poverty and unemployment, urban sustainability, as well as climate and environmental change.